You can't do anything about it, but you can make the best of it: a qualitative analysis of pandemic-related experiences in six European countries - Zrnić Novaković, Irina; Lueger-Schuster, Brigitte; Verginer, Lucia; Bakić, Helena; Ajduković, Dean; Borges, Camila; Figueiredo-Braga, Margarida; Javakhishvili, Jana (Darejan); Tsiskarishvili, Lela; Dragan, Małgorzata; Nagórka, Nadia; Anastassiou-Hadjicharalambous, Xenia; et al. (European journal of psychotraumatology, 2022)
The complex system of stressors related to the coronavirus disease 2019 (COVID-19) pandemic has affected the global population, provoking a broad range of psychological reactions. Although numerous studies have investigated the mental health impact of COVID-19, qualitative research and cross-country comparisons are still rare. This qualitative study aimed to explore self-perceived challenges and opportunities related to COVID-19 across six European countries. The overall objective was to provide a differentiated picture of individual subjective experiences in the early stages of the pandemic. The present study included 7309 participants from Austria, Croatia, Georgia, Greece, Poland, and Portugal. We performed qualitative content analysis according to Mayring analyse open-ended questions regarding stressful events, positive and negative aspects of the pandemic, and recommendations to cope with the pandemic situation. MAXQDA software was used for data management and analysis. Participants' accounts were moderately consistent across the countries. The most prominent themes regarding stressful and negative pandemic aspects included: Restrictions and changes in daily life, Emotional distress, and Work and finances. Answers about positive pandemic consequences were mainly centred around the themes Reflection and growth, Opportunity for meaningful/enjoyable activities, and Benefits on interpersonal level. Key themes identified from participants' recommendations to cope with the pandemic included Beneficial behavioural adjustment, Beneficial cognitive-emotional strategies, and Social support. Participants experienced various challenges, but also shared several positive pandemic consequences and recommendations to cope with the pandemic. These first-hand data could inform mental health practices to promote well-being during COVID-19 and similar global challenges in the participating countries and possibly beyond. We examined COVID-19-related experiences in 7309 adults from six European countries. Besides challenges, participants identified many positive pandemic consequences. Participants' recommendations to cope with COVID-19 included behavioural and cognitive-emotional strategies.